Rejuvenating Chinese opera through the integration of technology: A qualitative study on Malaysian Chinese youth acceptance - Ang, Kok Yew (2023)
Chinese Traditional Performance such as the Chinese Opera is slowly turning into a dying performing art in Malaysia. With dwindling audience and fewer youths expressing interest in it, this intrinsic part of the Chinese heritage is on the verge of becoming extinct due to modernization. However, past studies on traditional performing art have indicated technology integration into the art would be able to rejuvenate it. This study seeks to explore the potential of integrating technology into Chinese Opera. This raises a couple of fundamental questions: Would the integration be able to rejuvenate Chinese Opera? Would it be able to cause the arts to be seen as contemporary rather than traditional? To address these issues, this study employed a qualitative method to explore the potential of technology integration in Chinese Opera and the acceptance towards it as a result of this integration. In order to do so, this research was conducted in two phases – Phase 1 (an overview of youth perception towards Chinese Opera) and Phase 2 (Malaysian Chinese youth’s perceptions towards opera after exposing them to videos of Chinese opera being played with some elements of technology). In phase 1, 9 focus group discussions involving young Chinese Malaysians were held to discover their acceptance of Chinese Opera and the factors that shape their views. They were then invited to a second focus group discussion session in Phase 2 and were shown videos of Chinese Opera performance with technology integration. Their views of such Chinese Opera performances were sought to observe their thoughts and insights. Through this study, the researcher examined the impact of technology integration into Chinese Opera by looking at Malaysian Chinese youth acceptance. It is hoped that by doing so, this study can contribute to the knowledge of rejuvenating traditional art through technology. The findings of this study show that the acceptance from the Malaysian Chinese youth towards Chinese Opera are very positive. As the youth audience is constantly looking for contemporary and fresh entertainment, the findings of this research indicates that the integration of technology into Chinese opera is capable of rejuvenating the identity of the performing art without affecting the fundamental values that define it. In conclusion, technology integration must be aligned with other aspects of Chinese Opera rejuvenation in order to help Chinese Opera to adapt so that it will be seen as culturally appropriate by Malaysian Chinese youth.